Concomitant Cannabis Misuse and Associations with Depression, Pain and Substance Misuse among Patients Prescribed Opioids - M. Aryana Bryan; Elizabeth Charron; Omolola Adeoye-Olatunde; Jennifer Brown; Udi Ghitza; T. John Winhusen; Gerald Cochran (MDPI AG, 2021)
Background: Cannabis use is common among individuals with pain who are prescribed opioids, occurring in approximately 10% of this population. This study aims to explore the relationship between non-medical cannabis use and other health risks among individuals filling opioids at community pharmacies. Methods: This study was an exploratory secondary data analysis of a National Drug Abuse Treatment Clinical Trials Network (CTN)-sponsored study, Validation of a Community Pharmacy-Based Prescription Drug Monitoring Program Risk Screening, examining the relationship between risky cannabis use and depressive symptoms, pain, overdose, and other substance misuse among individuals filling opioid prescriptions in community pharmacies (N = 1440). Results: Participants reporting moderate- to high-risk compared to low-risk cannabis use were more likely to report depressive symptoms (adjusted OR = 1.67, 95% CI = 1.11-2.56), history of overdose (adjusted OR = 2.15, 95% CI = 1.34-3.44), and moderate- to high-risk use of alcohol (adjusted OR = 2.10, 95% CI = 1.28-3.45), opioids (adjusted OR = 2.50, 95% CI = 1.67-3.76), sedatives (adjusted OR = 2.58, 95% CI = 1.72-3.86), stimulants (adjusted OR = 4.79, 95% CI = 2.83-8.01), and tobacco (adjusted OR = 3.60, 95% CI = 2.47-5.24). Conclusions: Community pharmacies may be valuable sites for identifying, studying, and intervening with substance use problems.